JAM‐A and ALCAM are therapeutic targets to inhibit diapedesis across the BBB of CD14+CD16+ monocytes in HIV‐infected individuals. Issue 2 (24th November 2014) - Williams, Dionna W.; Anastos, Kathryn; Morgello, Susan; Berman, Joan W.
Abstract : JAM‐A and ALCAM mediate the transmigration of CD14 + CD16 + monocytes into the CNS of HIV seropositive individuals. Abstract : Monocyte transmigration across the BBB is a critical step in the development of cognitive deficits termed HAND that affect 40–70% of HIV‐infected individuals, even with successful antiretroviral therapy. The monocyte subsets that enter the CNS during HIV infection are not fully characterized. We examined PBMC from HIV‐positive individuals from 2 distinct cohorts and enumerated monocyte populations, characterized their transmigration properties across an in vitro human BBB model, and identified surface proteins critical for the entry of these cells into the CNS. We demonstrated that the frequency of peripheral blood CD14 + CD16 + and CD14 low CD16 + monocytes was increased in HIV‐seropositive compared with ‐seronegative individuals, despite virologic control. We showed that CD14 + CD16 + monocytes selectively transmigrated across our BBB model as a result of their increased JAM‐A and ALCAM expression. Antibody blocking of these proteins inhibited diapedesis of CD14 + CD16 + monocytes but not of T cells from the same HIV‐infected people across the BBB. Our data indicate that JAM‐A and ALCAM are therapeutic targets to decrease the entry of CD14 + CD16 + monocytes into the CNS of HIV‐seropositive individuals, contributing to the eradication of neuroinflammation, HAND, and CNS viral reservoirs.